1990
DOI: 10.1161/01.str.21.11.1589
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cerebral hemorrhage after treatment with tissue plasminogen activator or streptokinase following embolic stroke in rabbits [corrected].

Abstract: We studied thrombolysis in an animal model of embolic stroke to determine the safety of tissue plasminogen activator and streptokinase. We occluded the middle cerebral arteries of 137 rabbits with radiolabeled blood clots and administered tissue plasminogen activator (n=49), streptokinase («=40), or saline (n=48) at various times after embolization. We assessed the rate of thrombolysis and cerebral hemorrhage 24 hours later. Both drugs were very effective in producing thrombolysis. Compared with saline, strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…17,18,21,22,25 We found that TLT could be administered safely either alone or in the presence of tPA because neither the monotherapy nor combination therapy affected hemorrhage rate compared with their respective controls. Treatments also did not alter hemorrhage volume compared with the embolized control group.…”
Section: Discussionmentioning
confidence: 80%
“…17,18,21,22,25 We found that TLT could be administered safely either alone or in the presence of tPA because neither the monotherapy nor combination therapy affected hemorrhage rate compared with their respective controls. Treatments also did not alter hemorrhage volume compared with the embolized control group.…”
Section: Discussionmentioning
confidence: 80%
“…We estimated thrombolytic efficacy by calculating the percentage of animals in each treatment group that had Ͻ20% of the total recovered radiolabel in the surface vessels of the right hemisphere of the brain at postmortem. 18 Thrombolysis was found in 49% of the tPA-treated rabbits (Figure 4), 5% of the tPA/control-treated rabbits, and 35% of the combination drug-treated rabbits. There was no measurable thrombolysis in the BB-94 -treated group.…”
Section: Thrombolysis Ratementioning
confidence: 96%
“…This success rate corresponds well with other studies involving this model. 3,4,14,17 Hemorrhage Rate, Types of Hemorrhage, and Hemorrhage Volume Tables 2 and 3 present the hemorrhage rate for the 6 different treatment groups included in this study. There was a statistically significant difference in hemorrhage rates (Table 2) between the vehicle/vehicle group and the vehicle/tPA group.…”
Section: Stroke Success Ratementioning
confidence: 99%